Multiband metamaterial microwave absorbers using split ring and multiwidth slot structure - Seng, Sim Man; Yeow, You Kok; Esa, Fahmiruddin; Dimon, Mohamad Ngasri; Khamis, Nor Hisham (Wiley Periodicals, Inc, 2018)
This article proposes a multiband metamaterial microwave absorber based on a split ring-slot structure. Both simulation and experimental measurements are carried out to obtain the scattering parameters which are used to retrieve the absorption coefficient, relative permittivity, and relative permeability. The influences on the absorption produced by geometrical dimensions, incidence angles and polarisation angles are investigated from 1.5 to 18.0 GHz. The results show that the absorber possesses three resonance peaks with absorption greater than 70% measured experimentally at 3.0, 5.8, and 11.0 GHz. The absorption performance is insensitive to the angle of incidence, θ up to 60.The absorption mechanisms are studied based on the surface current distribution, electric field distribution, and constitutive parameters (μr and εr). Furthermore, a mechanical mean using dielectric material to tune the absorption frequencies (up to 1.0 GHz of tuning range) and enhance the absorption bandwidth (up to 50%) is demonstrated.